The human right to a healthy environment - Knox, John H.; Pejan, R. (New York : Cambridge University Press, 2018)
'Two of the great achievements of international law have been to define the human rights integral to a life of dignity, freedom, and equality, and to develop rules and institutions that protect the global environment. Because these two areas of the law developed separately and at different times, the relationship between them was at first unclear'--
Includes bibliographical references and index.
Keywords: Environmental law, International; Human rights -- Environmental aspects